The Correlation Spiritual Intelligence of Nurse’s Toward Fulfillment of Spiritual Nursing Care at Bali Mandara Regional General Hospital - Nova Dwigita Andini, Dewa Ayu Made; Susanti, Ni Luh Putu Dina; Bhandesa, Asthadi Mahendra (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background : English Arial italic 9 terdiri dari Introduction, Method, result and Conclusion Fulfillment of spiritual nursing care is a form of holistic nursing care that is influenced by spiritual intelligence, in providing nursing care, nurses will not only focus on physical nursing care, but also approach holistic care, namely bio-psycho-social-spiritual because nurses are professional workforce in providing nursing care such as playing a role in helping healing and providing care among human beings. Objective : The purpose of this research is to determine the correlation spiritual intelligence of nurse’s toward fulfillment of spiritual nursing care at Bali Mandara Regional General Hospital. The type of quantitative research, is correlative analysis with a cross-sectional study approach involving 209 respondents selected by probability sampling technique namely random sampling, conducted in March-April 2023. The analysis used the Spearman rho test. The research instrument used a questionnaire. Based on the results of the study, it was found that the spiritual intelligence of nurse’s was in the high category (61.2%) and the fulfillment of spiritual nursing care was mostly in the high category (55%). Results:  the results of analysis by test Spearman rho’ shows that the spiritual intelligence of nurses is related to the fulfillment of spiritual nursing care with a moderate correlation (p-value 0.001 <0.05, r = 0.408). Conclusion : It can be concluded that there is a significant correlation the spiritual intelligence of nurse’s toward fulfillment of spiritual nursing care at the Bali Mandara Regional General Hospital with a positive correlation direction.